Simplify i do not understand this and i need help

4x-(2-3x)-5 can be written as 4x-1(2-3x)-5

Use the distributive property. **NOTE: Distributive property helps to get rid of the parenthesis. a(b + c) = ab + ac**

Multipy the negative 1 into what is inside the parenthesis. 4x**-1(2-3x)**-5

-1*2=-2 and -1*-3x=3x, so -1(2-3x)=-2+3x

so now it's simplified to --> 4x-2+3x-5

Now combine like terms, 4x+3x=7x and -2-5=-7, this simplifies to..--> 7x-7

**7x-7** is the simplified way of writing 4x-(2-3x)-5

Hope you understood :)